2012
DOI: 10.1002/jbm.a.34188
|View full text |Cite
|
Sign up to set email alerts
|

On the biocompatibility between TiO2 nanotubes layer and human osteoblasts

Abstract: Titanium and its alloys are the most popular biomaterials replacing hard tissues in implant surgeries. Clinicians are generally pleased by titanium mechanical properties and non-toxicity performances; on the other hand, there have been reported several cases of titanium implantation failure, phenomenon explained sometimes as "non adherence of human tissue to the metallic surface." Yet, researchers reported that titanium surfaces are favorable for osteoblasts adhesion. Therefore, titanium integration into the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…TiO 2 nanotubes found applications in different domains, such as: dye-sensitized solar cells, photo-catalysis, gas sensing, water splitting, ion-intercalation (insertion) devices, supercapacitors [10,13]. Titanium dioxide nanotubes are also used as a biomaterial for implants, drug delivery platforms, tissue engineering, and bacteria killing [14][15][16][17]. Previous investigations [18,19] have demonstrated that TiO 2 nanoarhitecture could control the behaviour of different cell types.…”
Section: Introductionmentioning
confidence: 98%
“…TiO 2 nanotubes found applications in different domains, such as: dye-sensitized solar cells, photo-catalysis, gas sensing, water splitting, ion-intercalation (insertion) devices, supercapacitors [10,13]. Titanium dioxide nanotubes are also used as a biomaterial for implants, drug delivery platforms, tissue engineering, and bacteria killing [14][15][16][17]. Previous investigations [18,19] have demonstrated that TiO 2 nanoarhitecture could control the behaviour of different cell types.…”
Section: Introductionmentioning
confidence: 98%
“…Controversial results were noticed about incorporation of HA within nanotubes as two authors [49,50] claim that ‘there is an obvious positive change in the spreading and viability of osteoblasts on HA coated ~45 - 50 nm titania nanotubes layer comparing to cells on pure titanium or TiO 2 nanotubes’ and in contrast Gu et al [51] reports on reduced proliferation on 90 nm nanotubules with HA compared to same nanotubes without HA.…”
Section: Discussionmentioning
confidence: 99%
“…TNTs have been synthesized by Papanicolaou et al on pure titanium sheets, using the electrochemical anodizing method (Portan, Kroustalli, Deligianni, & Papanicolaou, 2012;Portan, Papaefthymiou, Arvanita, Jiga & Papanicolaou, 2012). The main synthesis methods were presented in Section 27.4.2.3 of this chapter.…”
Section: Case Studies: Titanium Dioxide Nanotubes-manufacturing and Imentioning
confidence: 99%
“…The need for self-organization in interphase investigation at the nanoscale level brought the CNT articles CNT patents CNT/polymer articles CNT/polymer patents 1990CNT/polymer patents 1992CNT/polymer patents 1994CNT/polymer patents 1996CNT/polymer patents 1998CNT/polymer patents 2000CNT/polymer patents 2002CNT/polymer patents 2004CNT/polymer patents 2006 titanium dioxide (TiO 2 ) nanotube (also known as a titania nanotube or by the acronym TNT) to the attention of researchers. The electrochemical anodizing method is often applied for the synthesis of TNT layers, a type of self-organized substrate (Portan, Kroustalli, Deligianni, & Papanicolaou, 2012;Portan, Papaefthymiou, Arvanita, Jiga, & Papanicolaou, 2012;Yan-Tao et al, 2003). TNTs are extremely convenient when manufacturing multilayered hybrid nanocomposites because they allow the interaction of two nanostructured substrates, resulting in the creation of an interphase between them; titania hybrid nanocomposites permit the study of nanostructured interphases from a purely scientific viewpoint, and are promising for use in advanced applications.…”
Section: Introductionmentioning
confidence: 99%